Dual 500-μs wide pulse neuromuscular electrical stimulation enhancing sensorimotor cortical excitability - Zhao, Yun; Yan, Yanying; Zhang, Xiaoling; Xie, Guanghui; Yang, Renqaing; Zou, Shuaidong; Gao, Fengmei; Sun, Wencheng (Frontiers in Human Neuroscience, 2025)
BackgroundNeuromuscular electrical stimulation (NMES) is an effective tool to improve motor activation of patients with motor dysfunction. However, to enhance the cortical activities induced by NMES, the corresponding strategies should be carefully designed with optimal stimulation parameters. The aim of the present study is to investigate whether the pulse assignment with wide-pulse-based Variable Frequency Trains improves sensorimotor cortical excitability.MethodsA block-designed experiment was conducted with NMES delivering current to right biceps brachii muscle in nine healthy right-handed adults to evoke repetitive elbow flexion under similar kinetic parameters (p > 0.05). A new NMES pattern with the combination of wide-pulse and Variable Frequency Trains (wDFT, variable-frequency trains with 2-let frequency train) was set to compare with other NMES patterns, i.e., variable-frequency trains with narrow-pulse (nVFT, 8-let frequency train), constant-frequency trains with narrow-pulse (nCFT, one pulse), and CFT with wide-pulse (wCFT, one pulse). The excitability levels of sensorimotor regions were investigated based on beta event-related desynchronization (ERD) analysis.ResultsAlthough evoking similar elbow flexion movements, variable-frequency trains (VFT) could induce stronger cortical activities than constant-frequency trains (CFT). Moreover, the sensorimotor cortex responded significantly more preferably to the dual 500 μs wide pulse VFT (wDFT) stimulation pattern (p < 0.05). In general, VFT induced higher amplitudes and descending slopes of beta ERD than CFT did during evoking elbow flexion movements, among which wDFT induced the highest beta ERD intensity and its descending slope (p < 0.05). In addition, the current efficiency of VFT to modulate sensorimotor cortical activities was higher than that of CFT pattern.ConclusionThe VFT pattern, especially dual 500 μs wide pulse VFT, could enhance sensorimotor cortical excitability, and the central neural activities improvements may attribute to the fact that more afferent fibers are effectively activated. Therefore, our findings indicated the high potential of utilizing DFT with wide pulses to optimize NMES applications in motor rehabilitation.